2010
DOI: 10.2215/cjn.03600410
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Testosterone and Mortality in Male Hemodialysis Patients

Abstract: Background and objectives: Low serum testosterone levels in hemodialysis (HD) patients have recently been associated with cardiovascular risk factors and increased mortality. To confirm this observation, we investigated the predictive role of serum total testosterone levels on mortality in a large group of male HD patients from Turkey.Design, settings, participants, & measurements: A total of 420 prevalent male HD patients were sampled in March 2005 and followed up for all-cause mortality. Serum total testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 36 publications
(35 reference statements)
5
94
0
1
Order By: Relevance
“…Similar results were also found for free testosterone forms. To our knowledge, this is the first study looking at testosterone concentration versus cardiovascular outcomes in nondialysis CKD, and it complements previous reports linking testosterone with mortality in dialysis patients (7,8,17). However, contrary to our hypothesis, adjustment for FMD values did not significantly affect this relationship, implying that the association between testosterone and cardiovascular outcomes is not fully explained by mechanisms related to impaired vasodilation.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results were also found for free testosterone forms. To our knowledge, this is the first study looking at testosterone concentration versus cardiovascular outcomes in nondialysis CKD, and it complements previous reports linking testosterone with mortality in dialysis patients (7,8,17). However, contrary to our hypothesis, adjustment for FMD values did not significantly affect this relationship, implying that the association between testosterone and cardiovascular outcomes is not fully explained by mechanisms related to impaired vasodilation.…”
Section: Discussionsupporting
confidence: 65%
“…Low testosterone levels in apparently healthy male populations have been identified as a predisposing risk factor to increased mortality and cardiovascular comorbidity (6). It has recently been reported that low endogenous testosterone values were also associated with increased risk of death in male hemodialysis patients (7,8). Interestingly, testosterone deficiency in men undergoing hemodialysis has also been related to arterial thickening, atherosclerotic plaque occurrence, and reduced flowmediated dilation (FMD) (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although we relate our findings to studies demonstrating a causative role for prolactin, we acknowledge that our observational design cannot determine whether prolactin is a risk factor per se or an intermediate of a larger pathophysiological pathway. For instance, prolactin retention leads to inhibition of gonadotropic hormone production, and testosterone deficiency in male CKD patients has indeed been linked to increased IMT, atherosclerotic plaque occurrence, reduced FMD, systemic inflammation, cardiovascular risk, and mortality (19)(20)(21)(22)(23)(24). Conversely, increased prolactinemia could also be a consequence of decreased dopaminergic activity (8), which would in turn imply an increment in norepinephrine release and that may have adverse effects on endothelial function and on other organs, perhaps favoring myocardial hypertrophy, hypertension, and other cardiovascular comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…At present, little is known about the implications of hyperprolactinemia in CKD. This may be relevant because testosterone deficiency, partly a consequence of prolactin-induced inhibition of gonadotropins, has been associated with cardiovascular risk factors and mortality in CKD (19)(20)(21)(22)(23)(24). We hypothesized that prolactin retention in CKD may be a contributing factor to vascular derangements and worse (cardiovascular) outcomes, and we tested this in two independent materials with prospective follow-up, including a cohort of nondialysis CKD patients with assessments of flow-mediated dilation (FMD) and carotid intima-media thickness (IMT), as well as a cohort of prevalent hemodialysis patients with assessments of pulse wave velocity (PWV).…”
Section: Introductionmentioning
confidence: 99%
“…The total and free testosterone levels are typically reduced, although the binding capacity and concentration of sex hormonebinding globulin are normal 30,31) . Disturbances in the levels of sex hormones are associated with decreased fertility and libido in addition to increased morbidity and mortality [32][33][34] .…”
Section: Sex Hormonesmentioning
confidence: 99%